Bajo el negro velo de la ilegalidad. un análisis del mercado de esclavos dominicano 1746-1821 - José Luis Belmonte Postigo (Nuevo mundo - Mundos Nuevos, 2016)
The Dominican slave market was affected by illegality at the end of the colonial period. Difficulties to implement a legal slave trade and the different slave codes who ruled Santo Domingo after 1795 caused the slaveholders reaction. Masters didn’t hesitate in manipulate notarial records in order to preserve their properties.